Detection and enumeration of bacillus cereus in formula milk and ultra high temperature (UHT) treated milk products - Tong, Pui Mun (Universiti Malaysia Sarawak (UNIMAS), 2015)
Bacillus cereus (B. cereus) is an important food borne pathogen that is widely distributed in nature. B. cereus has been isolated from many foods including dairy products, vegetables, meat and rice which often lead to outbreaks occurring in the world. Presence of B. cereus in milk products such as formula milk and UHT milk is of particular concern considering the majority of consumers are infants and children. The aim of this study was to enumerate and detect the presence of B. cereus in both formula milk (n=12) and UHT milk (n=20) sold in retail markets in Malaysia by employing a combination of MPN and PCR approach. Of all the samples tested, 41.67% (5/12) and 30% (6/20) were detected with B. cereus in formula milk and UHT milk respectively. Contamination level of B. cereus in formula milk ranged from < 3 to > 1100 MPN/g. Similarly, the level of contamination was also in the range of < 3 to > 1100 MPN/mL in UHT milk samples. The contamination level of B. cereus was found to be highest in full cream UHT milk and young-child formula. Therefore, it is crucial for the health and food safety authorities to address this issue as higher contamination level may be present in similar milk products.